2006
DOI: 10.1677/jme.1.02057
|View full text |Cite
|
Sign up to set email alerts
|

The hormone replacement therapy drug tibolone acts very similar to medroxyprogesterone acetate in an estrogen-and progesterone-responsive endometrial cancer cell line

Abstract: Tibolone, a steroidogenic compound with both estrogenic and progestagenic properties, is used as an alternative for estrogen or estrogen plus progesterone hormone therapy for the treatment of symptoms associated with menopause and osteoporosis. We have evaluated whether the effect of tibolone on a human endometrial cell line is similar to, or comparable with, the effect of estradiol (E 2 ), medroxyprogesterone acetate (MPA) or E 2 CMPA treatment. Using stable transfection techniques, the estrogen receptor (ER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The estrogen and progesterone responsive, well-differentiated human endometrial cancer cell line ECC1-PRAB72 23 was treated with estradiol or tamoxifen for 0, 1, 6, 24, 48, or 72 hours.After treatment, total RNA was isolated, and genomewide gene expression was measured using the Affymetrix U133 plus 2.0 GeneChip. Genes were selected that showed a 2-fold difference from the average control values in at least 1 time point (there were approximately 3200 genes meeting this criterion).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estrogen and progesterone responsive, well-differentiated human endometrial cancer cell line ECC1-PRAB72 23 was treated with estradiol or tamoxifen for 0, 1, 6, 24, 48, or 72 hours.After treatment, total RNA was isolated, and genomewide gene expression was measured using the Affymetrix U133 plus 2.0 GeneChip. Genes were selected that showed a 2-fold difference from the average control values in at least 1 time point (there were approximately 3200 genes meeting this criterion).…”
Section: Resultsmentioning
confidence: 99%
“…ECC1-PRAB72 cells (parental ECC-1 cells stably transfected with progesterone receptor A and B) were generated and maintained as described earlier. 23 One week before the experiments started, cells were transferred to phenol red-free DMEM/F12 supplemented with 5% dextrancoated charcoal-treated fetal bovine serum.The following hormones and hormone-like compounds were used: estradiol (E2), 4OH-tamoxifen (Tam), IGF-1 (Sigma-Aldrich Chemie BV, Zwijndrecht, the Netherlands), and human recombinant AREG (R&D Systems, Abingdon, UK).…”
Section: Cell Culturementioning
confidence: 99%
“…It is suggested that E 2 induces VEGF and SDF-1 production through ER in ESCs (14,23). Progestins are known to lead to down-regulation of ER in the human endometrium in vivo as well as in vitro, and therefore the inhibition of these angiogenic factors may be caused by the decrease in ER levels (18,35,37). Otherwise, ligand-occupied ER and PR bind directly to DNA at the steroid response element and recruit coregulators that activate or repress transcription via interaction with the general transcription apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…The ECC-1/PRAB72 cell line is both estrogen- and progesterone-sensitive and was derived after transfection with the human progesterone receptor A (hPRA) and B (hPRB). 15 The RL-95-2 cell line expresses both the estrogen and the progesterone receptors. Both cell lines were maintained in Dulbecco’s-Modified Eagle’s Medium (DMEM) supplemented with 5% fetal bovine serum (FBS), 300 mmol/L l -glutamine, 5 μg/mL bovine insulin, 10 000 units/mL penicillin, and 10 000 μg/mL streptomycin under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%